Antimicrobial Resistance and Associated Risk Factors for Clostridium difficile in Patients Attending Tertiary Care Settings - Murad A. Mubaraki; Mubbashir Hussain; Faaiz Ul Hassan; Shahzad Munir; Fozia Fozia; Ijaz Ahmad; Fatima Bibi; Samia Sultan; Ziaullah Zialluh (Journal of Tropical Medicine)
To determine the incidence of antimicrobial-resistant emerging pathogens, Clostridium difficile, and its associated risk factors in tertiary care setups of Pakistan. This cross-sectional prospective study was conducted from January 2019 to December 2020, to determine the prevalence and antimicrobial resistance patterns of C. difficile strains isolated from 450 stool specimens of patients suffering from diarrhea hospitalized in tertiary care hospitals in Peshawar, Pakistan. The stool samples of the patients were processed for culture and detection of toxin A and toxin B by enzyme-linked immunosorbent assay (ELISA) and tpi PCR. The drug sensitivity test was performed for antibiotics including ampicillin, cefixime, cefepime, amoxicillin, nalidixic acid, sulpha/TMP (SXT), chloramphenicol, metronidazole, vancomycin, ciprofloxacin, levofloxacin, and imipenem. Of 450 stool specimens, 108 (24%) were positive for C. difficile by stool culture, whereas 115 (25.5%) were only positive for C. difficile toxins based on ELISA and PCR (128 (28.6%). Of 108, 90.7% (n = 98) isolates were resistant to one antibiotic, and 90 (83.4%) were resistant to three or more antimicrobials. The highest resistance rates were found against penicillin (83.3%) followed by amoxicillin (70%), nalidixic acid (61%), and metronidazole (38%), and the lowest resistance was found against vancomycin (6.4%) and imipenem (3.7%). CDI was statistically significantly correlated with increased age, use of antibiotics, abdominal surgeries, use of proton pump inhibitors and H2a, and presence of comorbidities. The high frequency of C. difficile in Peshawar, Pakistan, indicates that CDI is an important nosocomial infection in different hospitals. The results will be helpful for clinicians to redesign control and therapeutic strategies in hospitals.